THE HISTORY AND THEORETICAL FOUNDATIONS OF THE LEXICAL SYSTEM IN AUSTRALIAN ENGLISH - Muharramoy Boqieva (World Scientific Research Journal, 2025)
Australian English (AusE) represents a unique variety of the English language, shaped by historical, cultural, and social influences. This article explores the history and theoretical foundations of its lexical system, drawing on linguistic theories such as lexical borrowing, semantic shift, and sociolinguistic variation. Through a systematic review of historical texts and linguistic studies, we identify key phases in the development of AusE vocabulary, from colonial origins to contemporary innovations. The findings highlight the role of Indigenous languages, British dialects, and global influences in forming a distinct lexicon. Discussions address implications for language policy and identity in multicultural Australia. This review underscores the dynamic nature of lexical evolution in postcolonial Englishes.